Board Of Commissioners, Sharia Supervisory Board, ISR: Bank Size Moderation - Dewi, Mega Ayu Paundriyana; Rita, Maria Rio (LAA MAISYIR : Jurnal Ekonomi Islam, 2021)
The growth of Islamic Commercial Banks is not with the contribution of the community to Islamic banking. This study aims to determine whether through the size of the board of commissioners and the size of the sharia supervisory board, the Islamic Social Reporting Index (ISR) can be good for increasing the public’s awareness of Islamic Commercial Banks. This study uses quantitative methods with panel data regression analysis. The results show the board of commissioners and the sharia supervisory board have a large size so that the ISR can be wider. The moderating variable of bank size added in the study shows that the bank size cannot state that the bank has a large size of the board of commissioners and the size of the sharia supervisory board. The study concludes that the size of the board of commissioners and the sharia supervisory board can trigger banks to convey ISR properly.